INDIVIDUAL PREDISPOSITION AND TAX KNOWLEDGE: GENDER DIFFERENCE ON TAXPAYER COMPLIANCE OF BATIK MSME - Indra Kusumawardhani; Afni Sirait; Sri Luna Murdianingrum (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
Changes in the business world due to the COVID-19 pandemic have directly affected the Individual predisposition of business people. The government provides several economic stimuli so that the Indonesian economy and adjustments to tax regulations harmonization of tax regulations. Harmonization of tax regulations is expected to help income from the tax sector with taxpayer compliance in paying taxes. The purpose of this study is to analyze the individual predisposiotion of Batik SME’s in the Special Region of Yogyakarta in carrying out tax payment obligations due to the latest legislation harmonization of tax regulations. This research uses the method of purposive sampling with the number of respondents 50 male respondents and 50 womans respondents. Data were processed using WarpPLS 7.0 to aim of examining direct and indirect causal relationships as well as significant and insignificant ones. The results of the study explain that variableIndividual Predispositon male respondents did not affect taxpayer compliance even though the mediation variable Harmonization of Tax Regulations was added, while for woman respondents this had a direct effect. The tax knowledge variable is directly and significantly related to male and woman taxpayer compliance. The mediation variable Harmonization of Tax Regulations has a significant effect on male respondent taxpayer compliance, but the mediation variable provides an insignificant relationship so that this variable fully mediates for woman respondents.